Agency Problems and Dividend Policies around the World - La Porta, Rafael; Lopez‐de‐Silanes, Florencio; Shleifer, Andrei; Vishny, Robert W. (Journal of Finance, 2000)
This paper outlines and tests two agency models of dividends. According to the “outcome model,” dividends are paid because minority shareholders pressure corporate insiders to disgorge cash. According to the “substitute model,” insiders interested in issuing equity in the future pay dividends to establish a reputation for decent treatment of minority shareholders. The first model predicts that stronger minority shareholder rights should be associated with higher dividend payouts; the second model predicts the opposite. Tests on a cross section of 4,000 companies from 33 countries with different levels of minority shareholder rights support the outcome agency model of dividends.